Trojaka radość w buddyzmie - KOSIOR, Krzysztof (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
In the first and main part of the article, the author presents three kinds of joy described in the Pali Canon. The first one is part of the experience of sensual pleasure and ultimately turns out illusory. The second one comes to light and develops as a result of the practices recommended by Buddha, in particular as the fruit of the progress of meditation. The third one includes the greatest happiness inherent in the state of nirvana. In the second part of the article, the author describes the ways of inspiring joy and of relieving suffering, as they are described in the Mahayana, in particular those of them which are related to the idea of the transfer of merit. Translated by Dorota Chabrajska